Eksplorasi dan Pemetaan Potensi Wisata Kampung Batu Busuk, Kecamatan Pauh, Kota Padang - PK Dewi Hayati; Yonariza Yonariza; Rudi Febriamansyah; Eri Besra; Virtuous Setyaka (Warta Pengabdian Andalas, 2021)
Batu Busuk is a village adjacent to the Andalas University campus in Padang. The village, the centre of durian production in Padang city, has a variety of tourism attraction and destination. The purpose of this activity is to inventory and to map out all tourism potential in Batu Busuk and to map out the problems faced by tourism actors community organization in developing the destination. Based on the exploration carried out, the potential tourist attraction of Batu Busuk varies diversely, consisting of nature tourism, historic site tourism, agro-tourism and cultural tourism. However, there are some problems exist, i.e. lack of accessibility, lack of supporting facilities and institutions. Therefore, immediately efforts made are to prepare human resources, secondly to strengthen tourism management institution. Tourism service and other related services of Padang City can collaborate with local people and provide support in term of developing Batu Busuk tourism into a leading tourist destination in Padang.